Institutions in property market operation : a case study of the Johor Bahru industrial property market - Kamarudin, Norhaya (2004)
The property market is affected by the rules and it forms an important aspect in understanding the operation of the property market. This research investigates the functions of institutions in property markets operations. It examines the operation of the Johor Bahru industrial property markets in determining the organizations, performance and pattern of the property market activities. The philosophy of the research is based on the characteristics of the property market, which is information inefficient, decentralised and subjected to local laws and customs. These are best captured by the institutional economic approach, which defines institutions as 'rules of the game' for agents' network of relationship. Adopting the institutional framework of analysis, the research analyses the evolutionary changes in organizational form, performance and activities that emerged. The effect of institutions on the organizations of the property market is traced through the changing forms of the property market, which changes fiom an undeveloped market to a developed form to cater for a complex investment and use purposes. The economic and political influences are the main driving force shaping these changes and it forms the environment in which institutions are created. Consequently the changing form of property market organizations has also affected the performance of the industrial property market where the rise and fall of property values are the outcomes of the decisions of agents' interaction from the changing institutional structure. Findings also indicate that economic and policy influences have affected use, investment and development activities of the industrial property market. Changing industrial policy has given rise to small-scale industries, which attracts commercial property developers to construct flexible standard factory buildings. This has also change the market from a purely use market to an emerging investment market. Thus institutions have an important role in understanding how the property market operates as it determines property market behaviour.